Efektivitas Penyimpanan dan Pengelolaan Benda Sitaan Negara ( Studi Kasus : Rupbasan Kelas I Denpasar) - Manuaba, Ida Bagus Made Wedhana; Yudartha, I Putu Dharmanu (Socio-political Communication and Policy Review, 2024)
This research examines the effectiveness of RUPBASAN Class I Denpasar in storing and managing confiscated goods, identifying challenges faced, and evaluating efforts to overcome them. The problems faced include the complexity of the suspect's legal status which often slows down the process of managing confiscated objects and internal limitations such as a lack of employee competence. The research method used is a qualitative descriptive approach. Data was collected through interviews with related parties, direct observation at the location, and analysis of relevant documents. The analysis was carried out based on the theory of organizational effectiveness according to Richard M. Steers (I985), which includes organizational, environmental, worker and management characteristics. However, several obstacles such as budget limitations, lack of experts, and administrative challenges still affect operational effectiveness. Optimal management of confiscated goods requires increasing employee competency, strengthening coordination between agencies, and providing adequate facilities and infrastructure. This research provides recommendations for increasing the effectiveness of managing confiscated objects through increasing training, developing human resources, and adjusting budget policies. Thus, this research provides a significant contribution in understanding the dynamics and challenges of managing confiscated objects at RUPBASAN Class I Denpasar, as well as providing strategic recommendations to increase the operational effectiveness and efficiency of this institution. Abstrak Penelitian ini mengkaji efektivitas RUPBASAN Kelas I Denpasar dalam menyimpan dan mengelola barang sitaan, mengidentifikasi tantangan yang dihadapi, dan mengevaluasi upaya untuk mengatasinya. Masalah yang dihadapi antara lain kompleksitas status hukum tersangka yang sering memperlambat proses pengelolaan benda sitaan dan keterbatasan internal seperti kurangnya kompetensi pegawai. Metode penelitian yang digunakan adalah pendekatan deskriptif kualitatif. Data dikumpulkan melalui wawancara dengan pihak terkait, observasi langsung di lokasi, serta analisis dokumen yang relevan. Analisis dilakukan berdasarkan teori efektivitas organisasi menurut Richard M. Steers (I985), yang meliputi karakteristik organisasi, lingkungan, pekerja, dan manajemen. Namun, beberapa kendala seperti keterbatasan anggaran, kurangnya tenaga ahli, dan tantangan administratif masih mempengaruhi efektivitas operasional. Pengelolaan barang sitaan yang optimal memerlukan peningkatan kompetensi pegawai, penguatan koordinasi antar instansi, dan penyediaan sarana serta prasarana yang memadai. Penelitian ini memberikan rekomendasi untuk meningkatkan efektivitas pengelolaan benda sitaan melalui peningkatan pelatihan, pengembangan sumber daya manusia, dan penyesuaian kebijakan anggaran. Dengan demikian, penelitian ini memberikan kontribusi signifikan dalam memahami dinamika dan tantangan pengelolaan benda sitaan di RUPBASAN Kelas I Denpasar, serta memberikan rekomendasi strategis untuk meningkatkan efektivitas dan efisiensi operasional institusi tersebut. Kata Kunci : Efektivitas Kinerja, Rupbasan Kelas I Denpasar, basan dan baran.